2015
DOI: 10.1589/jpts.27.2113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the correlation between the contraction of the pelvic floor muscles and diaphragmatic motion during breathing

Abstract: [Purpose] This study was conducted to investigate the effect of the correlation between the pelvic floor muscles (PFM) and diaphragmatic motion during breathing. [Subjects] The subjects of this study were 20 healthy female students who listened to an explanation of the study methods, purpose and agreed to participate in the experiment. [Methods] Radiograph equipment was used to examine diaphragmatic motion with contraction of the PFM during breathing, and a spirometer was used to examine lung vital capacity. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 16 publications
0
54
0
3
Order By: Relevance
“…Studies have shown that pelvic floor muscles (PFMs) together with internal oblique, intercostal muscles, transverse abdominal muscle, and diaphragm are responsible for maintaining proper body posture and breathing [32,33]. Due to numerous myofascial connections between PFM and other muscles all movements are functionally linked, and throughout this system, PFM exists as the basis for local stabilization [33,34]. For this reason, myofascial disorders as well as posture disorders can lead to impaired PFM function and, consequently, their weakness and UI [35].…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
“…Studies have shown that pelvic floor muscles (PFMs) together with internal oblique, intercostal muscles, transverse abdominal muscle, and diaphragm are responsible for maintaining proper body posture and breathing [32,33]. Due to numerous myofascial connections between PFM and other muscles all movements are functionally linked, and throughout this system, PFM exists as the basis for local stabilization [33,34]. For this reason, myofascial disorders as well as posture disorders can lead to impaired PFM function and, consequently, their weakness and UI [35].…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
“…The pelvic floor (PF) is a well-defined muscular structure that plays a role in several important urological, gynecological, gastroenterological, and pulmonary functions 1 , 2 , 3 , 4 , 5 ) . Pelvic floor dysfunction (PFD) can lead to mild or even devastating consequences such as urinary incontinence (UI), fecal incontinence (FI), pelvic organ prolapse (POP) and sexual problems 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The reasons behind the disorders of pelvic oor muscles can be caused by dysfunctions in the pelvic area, 47 but the reasons can also be found elsewhere, for example in breathing. 48 Even though the exercise interventions seemed to be effective, the differences between intervention and control groups vanished in the late postnatal period. 24 This is an interesting nding, because the evaluations of the number of women suffering from disorders related to pelvic oor muscle function in the long term are quite high.…”
Section: Discussionmentioning
confidence: 99%